Budaya Mutu dalam Peningkatan Kinerja Pendidikan: Sebuah Kajian Sistematis atas Strategi Kepemimpinan dan Penjaminan Mutu di Lembaga Pendidikan (Lembaga Pengembangan Kinerja Dosen, 2025)
Improving the quality of education has become a strategic issue in efforts to strengthen the competitiveness and credibility of educational institutions in the era of globalization. One crucial approach to achieving this goal is developing a quality culture as a system of values, attitudes, and habits oriented towards continuous improvement. This article aims to systematically review how the concept of quality culture is applied in the educational context and answer the question: how do strategies for strengthening quality culture contribute to improving the performance of educational institutions? This research uses a qualitative approach using the Literature Review (LR) method. The data sources were scientific articles from 2020–2025 accessed through Google Scholar and Publish or Perish (PoP) with the keyword